CRL optics and silicon drift detector for P06 Microprobe experiments at 35 keV. (December 2020) - Falkenberg, Gerald; Seiboth, Frank; Koch, Frieder; Falch, Ken Vidar; Schropp, Andreas; Brückner, Dennis; Garrevoet, Jan
Abstract : A provisional setup for X-ray microprobe experiments at 35 keV is described. It is based on compound refractive lenses (CRLs) for nanofocusing and a Vortex silicon drift detector with 2 mm sensor thickness for increased sensitivity at high energies. The Microprobe experiment (PETRA III) generally uses Kirkpatrick-Baez mirrors for submicrometer focusing in the energy range of 5–21 keV. However, various types of scanning X-ray microscopy experiments require higher excitation energies. The CRL optics were characterized by X-ray ptychography and X-ray fluorescence (XRF) knife edge scans on a siemens star pattern and showed beam sizes down to 110 nm. The performance of the new setup for microscopic X-ray diffraction (XRD)–XRF scanning X-ray microscopy measurements at 35 keV is demonstrated on a cross-section of a painting fragment.